Enhancing Equity through Curriculum Differentiation Practice in Nepal (Solukhumbu Multiple Campus Research Journal, 2024)
Diversity is an inherent reality of today’s classrooms, where students represent a wide range of backgrounds, abilities, and socio-cultural dynamics. The issue of equity has gained significant attention from researchers and curriculum developers as they seek to address such diverse phenomena in the curriculum development process.  This study explored the status of equity through curriculum differentiation practice in the school, its major problems, and coping strategies for addressing the challenges. The study was conducted in two different types of schools (public and private) from Kathmandu Valley. Building on a qualitative research approach and case study design, four teachers from the two selected schools were purposively selected to derive the data. In this study, open-ended interviews, non-participant observation, and focus group discussions were used as the data collection tools. The obtained data were analyzed and interpreted using thematic analysis procedures. The findings show that there is enough practice of curriculum differentiation regarding the content, strategy and methods, learning environment, and student output in the schools. However, there are rare intentional practices of curriculum differentiation to promote equity in schools. Instead, these practices primarily focus on addressing the equity of the learners related to their learnability. The study also indicates that schools have faced some problems like poor resources, proper training, and collaborative instruction during the differentiation practice of curriculum. Therefore, equity can be enhanced in educational institutions through curriculum differentiation practices by effectively managing resources, providing adequate training, and fostering collaborative instruction. The study suggests that enhancing equity in schools requires not only the efforts of teachers but also the active involvement of administrators, parents, and students.